Complete mitochondrial genome of Ricania shantungensis Chou & Lu, 1977 (Hemiptera: Ricaniidae) - Hyobin Lee; Keon Hee Lee; Jeong Sun Park; Gwan-Seok Lee; Iksoo Kim; Wonhoon Lee (Mitochondrial DNA. Part B. Resources, 2021)
Ricania shantungensis Chou & Lu, (Hemiptera: Ricaniidae), is an invasive pest that attacks forest as well as agricultural trees. We sequenced the 15,358 bp long complete mitochondrial genome (mitogenome) of this species; it consists of a typical set of genes (13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes) and one major non-coding AT-rich region. The orientation and gene order of the R. shantungensis mitogenome are identical to that of the ancestral type found in majority of the insects. Bayesian inference (BI) phylogeny placed the R. shantungensis examined in our study, together with Ricania spp. in a group with the highest nodal support, forming the family Ricaniidae to which R. shantungensis belongs.